EFFECT OF SIMULTENEOUS TRANSMISSIONS PHENOMENON ON AIR TFAFFIC CONTROL SYSTEMS FUNCTIONALITY - D. V. Kolyadov; A. V. Prokhorov (Научный вестник МГТУ ГА, 2016)
In the paper the voice communication system functionality in case of simultaneous transmission phenomenon is analyzed. The functional algorithms of the VHF receiver and voice communication system are considered.